Digital Detention: Engagements in Collaborative Counter-Surveillance - Boe, Carolina Sánchez; Rodriguez, Jessie (Surveillance & Society, 2025)
Drawing on collaborative research with asylum seekers under digital surveillance in Austin, Texas, this photo essay discusses the experiences of—and resistance to—electronic monitoring through GPS monitors strapped on ankles or wrists and through the facial recognition app SmartLINK, which are deployed on migrants and asylum seekers by GEO Group, one of the world’s largest prison corporations for the US Immigrations and Customs Enforcement (ICE). The toolkits developed throughout the Digital Detention collaborative project constitute forms of collective counter-surveillance that make the consequences of this public/private partnership on migrants’ lives part of a larger conversation that contributes to making the economic logics of this kind of surveillance visible in the larger community that asylum seekers are both part of and excluded from.